2023
DOI: 10.3390/biomedicines11061608
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of the Anterior Cingulate Cortex and the Right Anterior Insula Differentiates between Major Depressive Disorder, Bipolar Disorder and Healthy Controls

Abstract: Background: This study aimed to explore possible differences of the whole-brain functional connectivity of the anterior cingulate cortex (ACC) and anterior insula (AI), in a sample of depressed patients with major depressive disorder (MDD), bipolar disorder (BD) and healthy controls (HC). Methods: A hundred and three subjects (nMDD = 35, nBD = 25, and nHC = 43) between the ages of eighteen and sixty-five years old underwent functional magnetic resonance imaging. The CONN Toolbox was used to process and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The postcentral gyrus, on the other hand, has been linked with the sensory-discriminative component of pain. In a previous study our research group found increased resting-state functional connectivity between the ACC and the postcentral gyrus in patients with depression in the context of both MDD and BD as opposed to healthy controls and we hypothesized that this finding may be interpreted as an impairment reflecting the signature of mental pain in depression ( 63 ). Moreover, a reduction of the gray-matter volume of the subgenual ACC was demonstrated in MDD but not in BD and healthy individuals which further supports the significance of this region for the etiopathophysiology of MDD ( 64 ).…”
Section: Discussionmentioning
confidence: 94%
“…The postcentral gyrus, on the other hand, has been linked with the sensory-discriminative component of pain. In a previous study our research group found increased resting-state functional connectivity between the ACC and the postcentral gyrus in patients with depression in the context of both MDD and BD as opposed to healthy controls and we hypothesized that this finding may be interpreted as an impairment reflecting the signature of mental pain in depression ( 63 ). Moreover, a reduction of the gray-matter volume of the subgenual ACC was demonstrated in MDD but not in BD and healthy individuals which further supports the significance of this region for the etiopathophysiology of MDD ( 64 ).…”
Section: Discussionmentioning
confidence: 94%
“…When the connections between the insula, cerebral cortex and Cbm are altered, emotions have a lesser positive impact on mood that tends, therefore, to subside [76]. Along with the insula, an additional brain area fundamental to the affective sphere is represented by the anterior cingulate cortex [94]. In this regard, it has been observed that patients with MDD exhibit a volumetric reduction of the grey matter at the level of this area, unlike those diagnosed with BD in which this decrease is evidenced in the Hip and Amg [94].…”
Section: Spinocerebellummentioning
confidence: 99%
“…Along with the insula, an additional brain area fundamental to the affective sphere is represented by the anterior cingulate cortex [94]. In this regard, it has been observed that patients with MDD exhibit a volumetric reduction of the grey matter at the level of this area, unlike those diagnosed with BD in which this decrease is evidenced in the Hip and Amg [94]. At the cerebellar level, the anterior cingulate cortex establishes relationships with both Crus I and Crus II, and in case of BD, these connections show reduced functional connectivity by confirming, once again, that the role of the Cbm cannot be limited to motor functions [94].…”
Section: Spinocerebellummentioning
confidence: 99%
“…Many neuroimaging studies observed the abnormal functional connectivity in ACC of MDD patients [ 8 , 9 ]. For example, a study from Bulgaria found the hyperconnectivity was existed between ACC and superior parietal lobule, lateral occipital cortex in MDD patients [ 10 ]. Another study found MDD patients emerged hyper-responses to loss outcomes in the ventral ACC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%